10 Bereavement training in the workplace, can it help bridge the grief support gap? A qualitative evaluation of employers' and employees' views. (14th March 2023) - Dewhurst, Felicity; Turner, Royce; Barrett, Laura; Wakefield, Donna; Hanratty, Barbara
Abstract : Background: Bereavement support is lacking and inequitable despite an excess need exacerbated by COVID-19 and recent reports highlighting the need for consistency. Literature has emphasised the key role communities including employers and public facing organisations could have in caring for the bereaved. Aims: To establish if bereavement training for employers and public facing organisations is beneficial, how it should be provided, to whom and whether associated policy change is required? Settin: In 2021 St Oswald's Hospice, Newcastle started providing bereavement training for employers and employees in public and private sector organisations. To date 343 participants from 105 regional and national organisations including local authorities, charities, universities, and health and emergency-service providers have been trained. Methods: Participants from the 105 organisations were asked for expressions of interest for participation in qualitative semi structured interviews. Purposive sampling selected 16 people ensuring data sufficiency and representation from all employment sectors. Results: Results were organised around four main themes: The unique challenges faced by employees and employers following a bereavement, the gap in bereavement training provision (including recommendations for inclusion and expansion), training should be tiered and bespoke (but basic training should be universally received) and change in (organisational and governmental) bereavement policies are required. Conclusions: Employees of varying grades and professions recommend tiered bereavement training for employing organisations. Perceived benefits include improved support and subsequently mental and physical wellbeing of employees, harmonious and efficient organisations and the development of supportive and compassionate communities. Recommendations for organisational and governmental bereavement policies include paid leave as standard with flexibility to respond appropriately to individual situations.